Abundant glial alpha-synuclein pathology in a case without overt clinical symptoms - Parkkinen, L; Hartikainen, P; Alafuzoff, I (Dustri-Verlag, 2007)
Screening of 1,800 brains with alpha-synuclein (alphaS) immunohistochemistry revealed five cases with abundant glial cytoplasmic inclusions (GCIs) within the white matter of the brainstem. Surprisingly, retrospective clinical assessment showed that one of these subjects did not fulfil the currently recommended clinical consensus criteria for the multiple system atrophy (MSA). One of the hallmark lesions of MSA, alphaS-positive GCIs, were widespread and abundant in this atypical case that nonetheless lacked any significant neuronal loss. If the patient had met the clinical criteria for MSA, the neuropathological phenotype would have undeniably confirmed the clinically suggested diagnosis. However, lacking overt clinical signs of MSA, the neuropathological phenotype in this subject is prone to be variably denoted or overlooked. We would therefore like to advise neuropathologists to acknowledge these cases with "occult" alpha-synucleinopathy and to inform the clinicians of such a finding. Whether these cases represent a preclinical stage of MSA or simply a biological coincidence, is yet unknown. The observation of abundant GCIs in an asymptomatic subject is, however, important, because even if these cases are rare in number, their occurrence challenge the current presumption, whereby simply the number of alphaS-positive GCIs mediates the neuronal dysfunction responsible for the clinical symptoms of MSA.